Pengolahan Limbah Cair Industri Alkohol Bekonang Menggunakan Proses Fermentasi - Budi_Utami, Karina Nurcahyani A - (Prosiding KPSDA, 2015)
This study aims to determine: (1) Wastewater treatment Bekonang alcohol industry using fermentation methods; (2) The content of wastewater alcohol Bekonang; (3) Glucose levels contained in wastewater alcohol Bekonang; (4) The optimum time alcoholic fermentation of liquid industrial waste Bekonang to produce the highest ethanol content. This study used an experimental method. Alcohol industry wastewater comes from Sembung, Bekonang, Mojolaban, Sukoharjo . The first step is to test the alcohol industry wastewater Bekonang with benedict test, Seliwanoffs test and the iodine test. Then analyzing glucose levels using Somogyi Nelson method. The second stage is fermentation process, namely in the form of liquid waste mixing with 0,529 grams of urea, NPK much as 0,106 g and 0,212 g Saccaromyces cerevisiae as to the erlenmeyer. Erlenmeyer sealed and allowed to stand for 24 , 48 , 72 , 96 and 120 hours. For the standing variation, waste water settling in advance for 2 , 6 and 10 days and then fermented for 96 hours . The third stage is the process of distillation of the fermented at a temperature of 70-800C. The last stage is to determine the concentration of ethanol by using Gas Chromatography (GC) by comparing the area of standards and an area of the sample. Based on this study it can be concluded that : (1) Waste water treatment Bekonang alcohol industry can use the method of fermentation to produce ethanol again; (2) Alcohol industry wastewater containing dextrin identified by test benedict , Seliwanoffs test and test iodine; (3) Glucose contained in wastewater alcohol Bekonang is 1,3285 %; (4) The optimum time alcoholic fermentation of liquid industrial waste Bekonang is 96 hours due to ethanol results obtained showed the highest ethanol content is 81.83 %